The Voice of The Heart of Community Mental Health Lay educators: Between Honesty and Challenge - Ira Kusumawaty; Suzanna Suzanna; Yunike Yunike; Yudi Abdul Majid (Universitas Aisyah Pringsewu, 2023)
Mental health lay educators in the community as extensions of health workers in community health centers play an essential role in mental health programs because of the ease of reaching, close access, and understanding of the socio-cultural values of the community. However, the complexity of the problem of the performance of mental health lay educators who are shrouded in stigma has not been explored in depth, even though this fact has a tremendous impact on the recovery of the condition of people with mental disorders undergoing treatment at home. It is vital to conduct a study by exploring the experience of mental health lay educators while assisting the community in caring to increase the productivity of people with mental disorders. The purpose of this study was to identify the experiences of mental health lay educators while carrying out their duties in the community. This research is a qualitative study by applying a phenomenological empirical approach as well as direct interviews based on time agreements between researchers and informants and observing the activities of the cadres. Through the use of a purposive sampling technique, informants were gathered. The saturation of the study was obtained after conducting interviews with 6 participants. The data analysis process was carried out using the Haase adaptation of the Colaizzi method to analyze the transcripts. The data analysis revealed four themes: various sad stories on duty, beautiful and fun stories, strands of hope as mental health lay educators, and descriptions of reasons for lay educators to persist. It is hoped that this experience will become input for community mental health program holders to pay special attention to the holistic needs of health lay educators to display their optimal performance. Abstrak: Kader kesehatan jiwa di masyarakat sebagai perpanjangan tangan tenaga kesehatan di pusat kesehatan masyarakat berperan penting dalam program kesehatan jiwa, karena kemudahan menjangkau, akses kedekatan serta pemahaman nilai sosial budaya masyarakat. Namun demikian kompleksitas permasalahan kinerja kader kesehatan jiwa yang diselimuti stigma masih belum tereksplorasi secara mendalam, padahal fakta tersebut berdampak luar biasa bagi pemulihan kondisi orang dengan gangguan jiwa yang menjalani perawatan di rumah. Penting untuk dilakukan kajian dengan mengeksplorasi pengalaman kader kesehatan jiwa selama mendampingi komunitas dalam merawat sehingga dapat meningkatkan produktivitas orang dengan gangguan jiwa. Tujuan penelitian ini utuk mengidentifikasi pengalaman kader kesehatan jiwa selama melaksanakan tugas di masyarakat. Penelitian ini merupakan studi kualitatif dengan mengamplikasikan pendekatan fenomenologi empiris serta mewawancarai langsung berdasarkan kesepakatan waktu antara peneliti dengan informan serta mengobservasi aktivitas para kader. Informan direkrut melalui teknik purposive sampling. Satusasi penelitian diperoleh setelah melakukan wawancara terhadap 6 partisipan. Proses analisis data dilakukan menggunakan adaptasi Haase dari metode Colaizzi digunakan untuk menganalisis transkrip. Berdasarkan analisis data diperoleh empat tema yaitu berbagai cerita menyedihkan dalam bertugas, kisah indah dan menyenangkan, untaian harapan sebagai kader kesehatan jiwa, uraian alasan kader tetap bertahan. Diharapkan pengalaman ini menjadi masukan bagi pemegang program penanganan kesehatan jiwa komunitas untuk memperhatikan secara khusus terhadap kebutuhan holistik kader kesehatan agar dapat menampilkan kinerja optimalnya.